Pharyngeal Colonization Dynamics of Haemophilus influenzae and Haemophilus haemolyticus in Healthy Adult Carriers - Mukundan, Deepa (American Society for Microbiology, 2007)
Haemophilus influenzae is an important cause of respiratory infections, including acute otitis media, sinusitis, and chronic bronchitis, which are preceded by asymptomatic H. influenzae colonization of the human pharynx. The aim of this study was to describe the dynamics of pharyngeal colonization by H. influenzae and an intimately related species, Haemophilus haemolyticus, in healthy adults. Throat specimens from four healthy adult carriers were screened for Haemophilus species; 860 isolates were identified as H. influenzae or H. haemolyticus based on the porphyrin test and on dependence on hemin and NAD for growth. Based on tests for hemolysis, for the presence of the 7F3 epitope of the P6 protein, and for the presence of iga in 412 of the isolates, 346 (84%) were H. influenzae, 47 (11%) were H. haemolyticus, 18 (4%) were nonhemolytic H. haemolyticus, and 1 was a variant strain. Carriers A and B were predominantly colonized with nontypeable H. influenzae, carrier C predominantly with b(−) H. influenzae mutants, and carrier D with H. haemolyticus. A total of 358 H. influenzae and H. haemolyticus isolates were genotyped by pulsed-field gel electrophoresis (PFGE) following SmaI or EagI digestion of their DNA, and the carriers displayed the following: carrier A had 11 unique PFGE genotypes, carrier B had 15, carrier C had 7, and carrier D had 10. Thus, adult H. influenzae and H. haemolyticus carriers are colonized with multiple unique genotypes, the colonizing strains exhibit genetic diversity, and we observed day-to-day and week-to-week variability of the genotypes. These results appear to reflect both evolutionary processes that occur among H. influenzae isolates during asymptomatic pharyngeal carriage and sample-to-sample collection bias from a large, variable population of colonizing bacteria.